Transient Response Performance Test on Aftermarket Motorcycle Rear Suspension in Indonesia - Desmas Arifianto Patriawan; Miftahul Ulum; M Sulton Alqoroni; Ahmad Yusuf Ismail (Journal of Mechanical Engineering, Science, and Innovation, 2021)
Modification parts are found in Indonesia, one of which is suspension. This paper proves which after-market suspension has the best performance. These three suspensions were tested with a transient response with a test instrument that has an excitation height of 30 mm with a shaft rotational speed of 322 rpm. The observed responses are displacement and settling time. The test results without the addition of mass obtained a displacement of 25 mm for Aspira, 39 mm for AHM and 39 mm for Combiz. The addition of 30 kg mass resulted in 29 mm for Aspira, 38 mm for AHM and 23 mm for Combiz. Settling time without adding mass 1 s for Aspira and 1.2 s for AHM and 0.9 s for Combiz. With the addition of 30 kg mass obtained settling time of 1.3 s for Aspira, 1 s for AHM and 0.7 s for Combiz.